MAAT: a new nonparametric Bayesian framework for incorporating multiple functional annotations in transcriptome-wide association studies - Han Wang; Xiang Li; Teng Li; Zhe Li; Pak Chung Sham; Yan Dora Zhang (Genome Biology)
Abstract Transcriptome-wide association study (TWAS) has emerged as a powerful tool for translating the myriad variations identified by genome-wide association studies (GWAS) into regulated genes in the post-GWAS era. While integrating annotation information has been shown to enhance power, current annotation-assisted TWAS tools predominantly focus on epigenomic annotations. When including more annotations, the assumption of a positive correlation between annotation scores and SNPs’ effect sizes, as adopted by current methods, often falls short. Here, we propose MAAT expanding the horizons of existing TWAS studies, generating a new model incorporating multiple annotations into TWAS and a new metric indicating the most important annotation.